The impact of the transport sector on the Tunisian national economy: an input–output analysis - Manel Daldoul; Ahlem Dakhlaoui (Discover Sustainability)
Abstract This paper investigates the economic impact of the Tunisian transportation sector using input–output (I–O) analysis. Our objective is to analyse the interdependencies between the transportation sector and other economic sectors, focusing on the four major modes of transportation: road, air, water and auxiliary transport services, considering them as exogenous, and then determining their impacts. Five key economic impacts are quantitatively derived over the period 2009–2017: forward linkage, backward linkage, production-inducing, supply shortage and sectorial price effects. The results show that the Tunisian transportation sector plays a crucial role in boosting other sectors of the national economy. Its robust capacity to attract and stimulate other industries makes it a key driver of economic growth and development. Road transportation has the highest production inducing effects indicating its important role in stimulating production in other sectors over the years. It also has the highest impact on employment, followed by air transport and auxiliary transport services. This underscores the importance of investing in and optimizing this mode of transportation to maximize its positive impact on the national economy.